1993
DOI: 10.1099/0022-1317-74-7-1357
|View full text |Cite
|
Sign up to set email alerts
|

Protection against ocular and cutaneous infection with herpes simplex virus type 1 by intragastric immunization with live virus

Abstract: Intragastric administration of live herpes simplex virus type 1 (HSV-1) was assessed for the induction of humoral immune responses and for protection against ocular and cutaneous challenge with virus. Mice showed no clinical abnormalities following intragastric inoculation with three different strains of virus (Miyama +GC, SC16, and P2C6, a thymidine kinase-defective mutant). Replication of virus was not detected in the oesophagus, superior cervical ganglia or coeliac ganglia of such animals and latent infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Like Irie et al (1992Irie et al ( , 1993, we did not detect replicating virus within the mucosa or submucosa of the digestive organs examined, including the oesophagus. Sampling errors might account for our inability to detect superficial foci of viral infection; alternatively, a major site of mucosal involvement may occur distal to the duodenum.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Like Irie et al (1992Irie et al ( , 1993, we did not detect replicating virus within the mucosa or submucosa of the digestive organs examined, including the oesophagus. Sampling errors might account for our inability to detect superficial foci of viral infection; alternatively, a major site of mucosal involvement may occur distal to the duodenum.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, Irie et al (1992Irie et al ( , 1993) described a method of oral immunization against subsequent lethal herpesvirus challenge by directly placing (using a canula) infectious HSV-1 into the stomachs of mice. Mice tolerated the immunization procedure well and the authors found that the inoculum could no longer be detected in the stomach within minutes of gastric inoculation and had presumably been inactivated by gastric secretions.…”
Section: Discussionmentioning
confidence: 99%
“…They are trapped in the nasal, oral or gut epithelium and stimulate peripheral mesenteric, gut-asso ciated, mammary gland and/or splenic lymphocytes [61,62], These committed lymphocytes migrate through the peripheral blood system and home in on the lacrimal glands, CALT, cornea and other inflammatory sites [63]. Consistent with this pattern, when the virus-infected mu cosal membrane is in a remote site or viral vaccine is administered via an intranasal, oral, gastric or vaginal route, specific tear IgA antibody increases and generates ocular surface protection [64,65], Anti-viral IgG and IgM also increase in the tear film. Although quiescent eyes sometimes express antibody activity against HSV, vari cella, CMV, EBV, measles, rubella, mumps, adenovirus, influenza, rhinovirus and HIV in tears, the concentration of these antibodies increases significantly upon exposure to an actual viral infection [66][67][68], S-IgA mediates the major antiviral function of mucosal immunity.…”
Section: Ocular Secretory Immune Responsesmentioning
confidence: 57%
“…Tears contain various antiviral S-IgA antibodies. They are secreted by the antigen-sensitized SIgA-committed antibody-forming cells which have mi grated from a remote site (MALT) and are destined to lodge in the lacrimal gland or CALT [95], a picture which is sup ported by a number of oral immunization studies with live HSV, adenovirus, poliovirus, and CMV vaccine [64], Re cent developments in biotechnology enable the manufac ture of effective virus components or viral polypeptides as vaccines encapsulated in adjuvant-like delivery systems such as liposomes or biospheres [96]. These can be deliv ered to MALT orally, inhaled through the nasal mucosa or even injected subconjunctivally and enhance both the humoral and cellulararms of immunity.…”
Section: Strategies For Future Immunotherapymentioning
confidence: 99%
“…The mice were clinically evaluated on days 2, 5, 7, 9, 12, 15 and 21 after corneal inoculation. Cornea, iris and lids of animals were examined for signs of disease (Irie et al, 1993). Criteria for keratitis include mydriasis, iris hyperaemia, corneal ulceration, ground glass cornea and stromal opacity.…”
Section: Clinical Observations Of Corneal Disease Progressionmentioning
confidence: 99%